A six sigma approach to sustainability continual improvement for social responsibility - Duckworth, Holly Alison 1963-; Hoffmeier, Andrea (Industrial innovation series)
Explains and demonstrates the meaning of CISR--continual improvement for social responsibility--and illsutrates the six-step SOFAIR methodology with many examples"--Back cover